Efektivitas Model Pembelajaran Direct Instruction Terhadap Pembentukan Karakter Disiplin Siswa pada Mata Pelajaran PJOK di SMP Negeri 1 Pangatikan - Gunawan Gunawan; Irwan Hermawan; Alam Hadi Kosasih (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to analyze the effectiveness of the Direct Instruction learning model in developing students’ discipline character in Physical Education, Sports, and Health (PJOK) at SMP Negeri 1 Pangatikan. The study employed a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 30 students selected through purposive sampling. Data were collected using a discipline character questionnaire and analyzed through descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, and the N-Gain test. The results showed that the mean score of students’ discipline character increased from 76.37 in the pretest to 115.07 in the posttest. The Wilcoxon Signed Rank Test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. Furthermore, the N-Gain analysis produced an average score of 0.7035 (70.35%), which falls into the high category. These findings indicate that the Direct Instruction learning model is effective in improving students’ discipline character through structured learning activities, clear instructions, and continuous feedback. Therefore, the Direct Instruction model can be considered an alternative learning strategy in PJOK to support the development of students’ discipline character